PENGARUH MODEL PROJECT BASED LEARNING (PJBL) TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI BANGUN RUANG DI SEKOLAH DASAR - Umayroh, Rizki; Siregar, Nurdiana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The purpose of this study is to identify the impact of the project-based learning model on students' critical thinking skills in building space materials in elementary schools. Initial tests revealed that most of the students in grade V of SDN 135562 Tanjung Balai City were still in the less critical criteria, with a percentage of 59%. Therefore, teachers need to use effective learning approaches, such as the Project Based Learning model, students' critical thinking skills can be improved. This study applies a quantitative method and uses a Quasi Experimental design in the form of a Nonequivalent Control Group Design. The research was carried out at SDN 135562 Tanjung Balai City with a total population of 140 students. This research uses an instrument to test critical thinking skills in the form of essays. The results show that the project-based learning model significantly affects the improvement of students' critical thinking skills. The hypothesis test with the t' test showed a value of -2.26 < 12.3 > 2.26 which showed that by rejecting the null hypothesis (H0) and accepting the alternative hypothesis (H1), it was proven that the Project Based Learning model had a positive impact on students' critical thinking skills in the building materials in elementary schools compared to using the conventional learning model. Keywords: Project Based Learning; Critical Thinking